Temporary meniscus extrusion is caused by cumulative stress from uphill and downhill tasks in healthy volunteers - Yosuke Ishii; Saeko Okamoto; Riko Okinaka; Takato Hashizume; Chen Xu; Kexin Zhu; Yuko Nakashima; Kaoru Okada; Kazuya Takagi; Nobuo Adachi; Makoto Takahashi (Frontiers Media S.A., 2024)
PurposeExcessive mechanical stress accumulates and causes knee injury. Meniscal extrusion is a key factor in detecting the reaction to cumulative mechanical stress. The accumulation of stress strongly depends on environmental conditions such as flat ground or uphill/downhill, and accumulates in knee compartments; only a few studies have reported the effects of different environments on lateral and medial meniscus extrusion. This study aimed to investigate the effects of cumulative uphill/downhill stress on the meniscal extrusion in each compartment.MethodsA total of 30 healthy volunteers with 30 affected knees were involved in this cohort study (mean age, 22.0 ± 1.1 years; men, n = 14). The participants were divided into flat-walking, uphill/downhill-walking, and uphill/downhill-jogging groups and their numbers of steps taken were recorded during the effort. Moreover, medial and lateral meniscal extrusions during walking were evaluated using ultrasound three times, before and after efforts (T1) and (T2), and one day after efforts (T3), respectively.ResultsIn the flat-walking group, no significant differences were observed between the follow-up periods. Conversely, in the uphill/downhill-walking and jogging groups, the medial meniscus extrusion at T2 was significantly higher than that at T1. Conversely, the medial meniscus extrusion at T3 was significantly lower than that at T2. By contrast, the lateral meniscus did not show any difference between the follow-up periods in any group.ConclusionTemporary extrusion of the meniscus occurred after uphill/downhill tasks in healthy volunteers, and its reaction was observed only in the medial meniscus.